Sustainable science and intelligent technologies for societal development - Mishra, Brojo Kishore 1979- (IGI Global, 2023)
"In today's world, the pressing challenges of sustainable development and societal progress demand innovative solutions that harness the power of science and technology. From climate change to resource depletion and social inequalities, the urgency to find sustainable, intelligent, and ethical approaches has never been greater. Academic scholars and researchers play a crucial role in driving these advancements but often struggle to find comprehensive resources that bridge the gap between theory and real-world applications. The need of the hour is a definitive guide that unites expertise from diverse disciplines and offers practical insights into leveraging sustainable science and intelligent technologies to create meaningful societal development. Sustainable science and intelligent technologies for societal development, edited by Brojo Kishore Mishra of GIET University, India, is the much-awaited solution to the challenges faced by academic scholars and researchers.
Keywords: Sustainable engineering; Sustainable development; Artificial intelligence / Industrial applications